164 Genome-wide DNA Methylation Profiling in in Utero Heat-stressed Pigs as Measured by Whole-genome Bisulfite Sequencing. (8th October 2021) - Brito, Luiz F; Maskal, Jacob M; Chen, Shi-Yi; Oliveira, Hinayah R; Graham, Jason R; Schinckel, Allan P; Johnson, Jay S
Abstract: In utero heat stress (IUHS) has several postnatal consequences in pigs that compromise health, increase stress response, and reduce performance. These phenotypes may be caused by epigenetic modifications such as DNA methylation, which are heritable molecular modifications that impact gene expression and phenotypic outcomes without changing the DNA sequence. Therefore, we aimed to compare the DNA methylation profiles between in-utero thermoneutral (IUTN) and IUHS pigs to identify differentially methylated regions. Twenty-four pregnant gilts were evenly assigned to either a thermoneutral (17.5 ± 2.1°C) or heat stress (cycling 26 to 36°C) chamber from d 0 to 59 of gestation, followed by thermoneutral conditions (20.9 ± 2.3°C) for the rest of gestation and until the piglets were weaned. At 105 d of age, 10 IUTN and 10 IUHS piglets were euthanized and Longissimus dorsi muscle samples were collected and used to perform whole-genome bisulfite sequencing (WGBS). Purified genomic DNA was fragmented and bisulfite conversion was performed. Illumina platforms were used to sequence WGBS libraries. All pigs had similar proportions of methylation at CpG sites. Two-hundred-sixty-eight genomic regions were differentially methylated between IUTN and IUHS pigs. These identified regions are located across all pig chromosomes and ranged from 2 (SSC18) to 40 (SSC10). Eighty-five unique differentially-methylated genes were identified. These genes have been reported to be involved in key biological processes such as transcriptional repressor activity and tRNA processing (e.g., SKOR2, TRMT6, TSEN2), cellular response to heat stress (e.g., CCAR2), placental vascularization (e.g., FZD5), central nervous system (e.g., VEPH1), cholesterol biosynthesis (e.g., CYB5R1), insulin receptor substrate (e.g., IRS2), synaptic transmission (e.g., RIMBP2), neurotrophic factor receptor activity (e.g., LIFR), immune response (e.g., CD84), DNA repair (e.g., CHD1L), and cell proliferation and endocrine signaling (e.g., SSTR1, CYB5R1). These findings contribute to a better understanding of the epigenomic mechanisms underlying postnatal consequences of IUHS in pigs.